Combination Therapy Targeting Both Tumor-Initiating and Differentiated Cell Populations in Prostate Carcinoma - Anna Dubrovska; Jimmy Elliott; Richard J. Salamone; Sungeun Kim; Lindsey J. Aimone; John R. Walker; J. P. Watson; Sauveur-Michel Maira; Carlos Garcı́a-Echeverrı́a; Charles Y. Cho; Venkateshwar A. Reddy; Peter G. Schultz (2010)
Abstract Purpose: The cancer stem cell hypothesis predicts that standard prostate cancer monotherapy eliminates bulk tumor cells but not a tumor-initiating cell population, eventually leading to relapse. Many studies have sought to determine the underlying differences between bulk tumor and cancer stem cells. Experimental Design: Our previous data suggest that the PTEN/PI3K/AKT pathway is critical for the in vitromaintenance of CD133+/CD44+ prostate cancer progenitors and, consequently, that targeting PI3K signaling may be beneficial in treatment of prostate cancer. Results: Here, we show that inhibition of PI3K activity by the dual PI3K/mTOR inhibitor NVP-BEZ235 leads to a decrease in the population of CD133+/CD44+ prostate cancer progenitor cells in vivo. Moreover, the combination of the PI3K/mTOR modulator NVP-BEZ235, which eliminates prostate cancer progenitor populations, and the chemotherapeutic drug Taxotere, which targets the bulk tumor, is significantly more effective in eradicating tumors in a prostate cancer xenograft model than monotherapy. Conclusion: This combination treatment ultimately leads to the expansion of cancer progenitors with a PTEN E91D mutation, suggesting that the analysis of PTEN mutations could predict therapeutic response to the dual therapy. Clin Cancer Res; 16(23); 5692–702. ©2010 AACR.